The Predictive Effect of Using Wayground as A Summative Assessment on Senior High School Students’ Learning Outcomes - Lilis Mei Cahyani; Achmadi Achmadi; Syamsuri Syamsuri; Maria Ulfah; Husni Syahruddin (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
Despite the increasing adoption of digital technology in education, summative assessments in many Indonesian high schools continue to rely on conventional methods that often limit student engagement and timely feedback, potentially affecting learning outcomes. Although, previous studies have explored gamified digital platforms for learning, empirical evidence on the predictive effectiveness of Wayground as a summative assessment tool in senior high school economics education remains limited. Therefore, this study examined the predictive effect of using wayground as a summative assessment on senior high school students’ learning outcomes at SMAN 2 Sungai Kakap. A quantitative survey design was employed involving 31 tenth-grade students selected through simple random sampling. Data were collected using validated and reliable questionnaires and documentation of students’ summative assessment scores. The data were analyzed using descriptive statistics and simple linear regression with IBM SPSS Statistics 25. This study found that the use of Wayground as a summative assessment is positively and significantly associated with senior high school students' learning outcomes (p < 0,001), with an R² value of 0,734.